Acoustic array systems : theory, implementation, and application - Bai, Mingxian; Ih, Jeong-Guon.; Benesty, Jacob (Singapore ; Hoboken : John Wiley & Sons, Inc., 2013)
Presents a unified framework of far-field and near-field array techniques for noise source identification and sound field visualization, from theory to application. Acoustic Array Systems: Theory, Implementation, and Application provides an overview of microphone array technology with applications in noise source identification and sound field visualization. In the comprehensive treatment of microphone arrays, the topics covered include an introduction to the theory, far-field and near-field array signal processing algorithms, practical implementations, and common applic.
Preface -- Acknowledgments -- Glossary: symbols and abbreviations -- 1. Introduction -- 2. Theoretical preliminaries of acoustics -- 3. Theoretical preliminaries of array signal processing -- 4. Farfield array signal processing algorithms -- 5. Nearfield array signal processing algorithms -- 6. Practical implementation -- 7. Time-domain MVDR array filter for speech enhancement -- 8. Frequency-domain array beamformers for noise reduction -- 9. Application examples -- 10. Concluding remarks and future perspectives -- Appendix: acoustic boundary element method.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Noise generators (Electronics); Microphone arrays; Sound analyzers; Noise -- Measurement; Noise control; TECHNOLOGY & ENGINEERING -- Acoustics & Sound; Microphone arrays; Noise control; Noise generators (Electronics); Noise -- Measurement; Sound analyzers; Electronic books